2008
DOI: 10.1007/s10592-007-9501-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence on the species status and phylogenetic relationships of Spiranthes parksii, an endangered orchid from Texas

Abstract: New genetic information on the taxonomic status of an endangered species may have strong implications for its continued protection and that of other listed taxa with questionable species status. While analyzing a more comprehensive project on the molecular phylogeny of North American Spiranthes (Orchidaceae), lack of genetic differentiation between endangered S. parksii, endemic only to Texas, and a common local congener, S. cernua, was discovered. To confirm these results in a comparative context, we focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…Similar to our conclusions, an investigation of the evolutionary distinctiveness of the federally listed narrowly endemic species Spiranthes parksii (Orchidaceae) from the more widespread Spiranthes cernua suggested the two be synonymized (Dueck and Cameron, 2008). The two species are often sympatric, possess many morphological similarities, and the differences that have been used historically to differentiate S. parksii were considered to reflect locally distinct phenotypes of the more widespread and variable S. cernua (Dueck and Cameron, 2008). Phylogenetic analyses of 3191 bp representing four DNA sequence loci showed S. parksii to be nested within S. cernua .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our conclusions, an investigation of the evolutionary distinctiveness of the federally listed narrowly endemic species Spiranthes parksii (Orchidaceae) from the more widespread Spiranthes cernua suggested the two be synonymized (Dueck and Cameron, 2008). The two species are often sympatric, possess many morphological similarities, and the differences that have been used historically to differentiate S. parksii were considered to reflect locally distinct phenotypes of the more widespread and variable S. cernua (Dueck and Cameron, 2008). Phylogenetic analyses of 3191 bp representing four DNA sequence loci showed S. parksii to be nested within S. cernua .…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, the authors recommended that the two species be synonymized but also stated that the impact of their results on the conservation of S. parksii ultimately rests with the USFWS. Although we have also suggested that synonymization is warranted, the conservation implications differ between our study and Dueck and Cameron (2008) given that A. decemloba populations also appear to be of conservation concern (see discussion below).…”
Section: Discussioncontrasting
confidence: 59%
“…Another example of the taxonomic uncertainties that complicate the conservation of Spiranthes is the disputed species status of federally endangered S. parksii Correll, which, as a peloric mutant, is likely to be only an aberrant local phenotype of widespread S. cernua (L.) Rich. (Dueck and Cameron, 2008). These are but a few cases in Spiranthes where having accurate taxonomic information for vulnerable species listed on ecological inventory checklists can have profound implications for habitat protection and conservation.…”
Section: Spiranthes Taxa Recognized In the World Monocot Checklist Rmentioning
confidence: 99%
“…This would provide sufficient genetic diversity to account for the amount of allozyme variation observed in this population (Schmidt and Antlfinger 1992). S. parksii Correll, described as a facultatively agamospermous tetraploid species endemic to postoak savannas in East Central Texas (Catling and McIntosh 1979;Sheviak and Brown 2002), is not distinct from S. cernua Dueck and Cameron 2008). Schmidt (1987) suggested that the high proportion of agamospermic seeds produced in eastern Nebraska populations of S. cernua might be due to pollinator limitation (discussed below under sexual populations) or to the precocious development of adventitious embryos prior to anthesis.…”
Section: Compatibility and Breeding Systemmentioning
confidence: 98%
“…Ten other Spiranthes taxa occur in North America north of Florida and Mexico: S. porrifolia Lindley (creamy ladies'-tresses), S. stellata P. M. Brown, Dueck, and Cameron (no common name), S. infernalis Sheviak (ash meadows ladies'-tresses), S. delitescens Sheviak (reclusive ladies'-tresses), S. longilabris Lindley (giant spiral ladies'-tresses), S. brevilabris Lindley (texas ladies'-tresses), S. floridana (Wherry) Cory (florida ladies'-tresses), S. eatonii Ames ex P. M. Brown (eaton's ladies'-tresses), S. praecox (Walter) S. Watson (greenvein ladies'-tresses), and S. sylvatica P. M. Brown (woodland ladies'-tresses), although the latter may not be distinct from S. praecox (Dueck and Cameron 2008). Nothing is yet known of their pollination biology.…”
Section: Additional Species Of Spiranthesmentioning
confidence: 99%